Critical Literacy: An Alternative Way in Language Classrooms - Pun-Iad, Suthiya (Journal of Humanities and Social Sciences Suratthani Rajabhat University, 2022)
Critical literacy is the method to consider how the texts appear in writing and speaking. It can manipulate text, images, sound, and various multimedia for questioning, including the thought, values, and beliefs produced by society. It focuses on learners which consist of 4 principles using critical literacy in the language classroom are: 1) generation, which is to generate the code, which defines the title, concept, or situation. It must be something that can allow learners to practice thinking and try to decipher it; 2) examination and creation, is to examine the information and create a critical framework from the subject or situation that the learner receives. By connecting them with their own experiences and values to lead to analysis and critique the subject or situation; 3) reflection, is to reflect the information gained from experience by expressing feelings, thoughts, or tone of things or situations; and 4) action and presentation, is to present solutions to problems through activities such as discussions, seeking answers. Presenting solutions for behavior change as well as creating their work or writing their text. Therefore, critical literacy is an alternative to organizing learning activities in the classroom language. So, the learners will improve their way of thinking and know the possibilities and possibilities of any situation in this complicated world.